Legal Protection of the Inheritance Rights of Wives and in Polygamous Marriages: A Review of Islamic Philantropy in the Manuscripts of Rozali-Buntet - Ridwan Ridwan (Lembaga Bale Literasi, 2025)
Legal protection of the inheritance rights of wives and children in polygamous marriages is an important issue in Islamic family law related to justice and welfare within the family. This study aims to analyze the form of legal protection of the inheritance rights of wives and children in polygamous marriages through reflections on Islamic philanthropy by examining the Rozali-Buntet manuscript as a living legal source in society. The method used is normative legal research with a regulatory, conceptualization, historical, and case approach. The data used is secondary data including primary, secondary, and tertiary legal materials. The results of the study indicate that normatively, Islamic law and the Compilation of Islamic Law have provided a clear basis for the distribution of inheritance, but in practice, inequality is still found due to social and cultural factors. The Rozali-Buntet manuscript shows a more flexible and contextual practice of inheritance distribution through a will mechanism, which reflects the values of justice and welfare. From the perspective of Islamic philanthropy, this distribution shows social concern and an effort to ensure the economic sustainability of the heirs. This research is expected to contribute to the development of Islamic family law in Indonesia, particularly in creating a more just, humanistic, and responsive inheritance distribution system to the needs of society.